2022
DOI: 10.20473/j.djmkg.v55.i2.p93-98
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antimicrobial peptide gel RISE-AP12 on decreasing neutrophil and enhancing macrophage in nicotine-periodontitis Wistar rat model

Abstract: Background: Periodontitis, an inflammation that causes alveolar bone destruction, is caused by bacteria and aggravated by nicotine exposure and is therefore a disease that many smokers have. Antibacterial agents are essential for the rejuvenation process in periodontitis treatment; antimicrobial peptide (AMP) gel is a broad-spectrum antibacterial agent that is hardly cause bacteria resistance. Purpose: The objective of this study is to determine the effect of AMP gel administration on neutrophil and macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…1 It has been shown that deep periodontal pockets as a result of alveolar bone destruction are associated with an increase in tooth loss. [2][3][4] Tooth loss, especially in the anterior area, can lead to psychological issues in some patients. 5 Aesthetical aspects must be taken into account during periodontal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…1 It has been shown that deep periodontal pockets as a result of alveolar bone destruction are associated with an increase in tooth loss. [2][3][4] Tooth loss, especially in the anterior area, can lead to psychological issues in some patients. 5 Aesthetical aspects must be taken into account during periodontal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is defined as a chronic inflammatory disease indicated by the infiltration of immune cells in the gingiva, which leads to connective tissue damage, clinical attachment loss, and resorption of the alveolar bone. 1,2 Poor oral hygiene and lifestyle choices lead to the onset and progression of periodontitis, one of the most prevalent chronic inflammatory diseases in humans. 3 Periodontitis is a risk factor for a number of diseases, such as infectious endocarditis, cardiovascular disease, fatal or nonfatal stroke, premature birth, diabetes mellitus, pulmonary disease, and sinus disease.…”
Section: Introductionmentioning
confidence: 99%
“…1 In general, periodontal disease is caused by bacterial plaque on a tooth's surface, where plaque is a thin layer of biofilm containing a collection of pathogenic microorganisms. 2 These pathogenic microorganisms can cause direct damage to periodontal tissue by activating the immune-inflammatory response but could also be beneficial bacteria in the periodontal pocket by providing sources of nutrition. 3 Supragingival plaque plays an important role in the growth, accumulation, and pathogenesis of subgingival plaque, especially in the early stages of the periodontal diseases gingivitis and periodontitis.…”
Section: Introductionmentioning
confidence: 99%